Sociabilidades e modos de vida em uma vila operária: o caso de Camaragibe (1900 – 1930) - Santos, Marcos Alesandro Neves dos (2023)
This doctoral thesis, entitled “Sociabilities and ways of life in a working-class village: the case of Camaragibe (1900-1930),” aims to verify the inner workings of and daily life of workers at the Fábrica de Tecidos de Camaragibe. Throughout the prese, we will analyze the implementation presente8f working-class villages in Brazil, the peculiarities of the spatial cut and its nuances, as well as the importance of Mutual Organization Societies and the Brazilian working worlds in the presente of the post-abolition of slavery. The religious presente present presente in the pages of this thesis, since – through the figure of Carlos Alberto de Menezes, who was the director of the factory and one of the biggest Catholic militants in Brazil at the time – he conditioned developments in the relationships between workers, as pres as the organizational concepts of “christian work organization”.Its is intend, therefore, to understand how workers, initially placed in labor organizations created by the bosses, re-signified these spaces, thurner them into spaces of resistance. This re-signification made it possible to verify that the traditional representation of the Fábrica de Camaragibe as na environment free of class struggle, strikes, of the demonstrations and what were considered “bad habits” did not match the daily lives of workers, as strikes and tensions did not fail to exist. Camaragibe’s workers may not meet the passionate expectations of militant historians who are always in search of major rupture movements, but their everyday life was marked by a constant “arm wrestling” that denotes a consciousness of themselves, their own and the presente in which they were presente.